The Mythologizing of Mark Twain - Beidler, Philip D.; Davis, Sara deSaussure (Book collections on Project MUSE., 1984)
Readers of Mark Twain seldom doubt his genius, but defining that genius and locating its source continue to challenge students of American literature. Equally elusive is an explanation of the intriguing phenomenon of Twain as a mythic figure, both shaper and embodier of an American mythos. Perhaps no single critical approach can adequately assess the complex force behind Samuel Clemens and Mark Twain. This native genius, our quintessential artist, rightfully provokes a number of powerful responses, as these original essays demonstrate.